Eva Fudali. Bryophyte species diversity and ecology in the parks and cemeteries of selected Polish cities. – Wroclaw: Agriculturali University of Wroclaw, 2005. – 212 p. (CHORNOMORSKI BOTANICAL JOURNAL, 2011)
Eva Fudali. Bryophyte species diversity and ecology in the parks and cemeteries of selected Polish cities. – Wroclaw: Agriculturali University of Wroclaw, 2005. – 212 p.